The prevalence of dental fluorosis and its associated factors in Salem district - Maya Ramesh; Malathi Narasimhan; Ramesh Krishnan; Paul Chalakkal; Rita Mary Aruna; Sarah Kuruvilah (Wolters Kluwer Medknow Publications, 2016)
Context: There are various regions in India that have high levels of fluoride in drinking water sources. Many people residing in such places suffer from dental fluorosis (DF). Aims: To evaluate the prevalence of DF in children residing in Salem and also to find any correlation between DF and other related factors. Materials and Methods: One school from each block of Salem (total 21 blocks) was selected for the study. A single examiner had evaluated untreated caries, lesions, and DF (for permanent anterior teeth and molars) using the Dean's fluorosis index, in all children. Water fluoride level determination at each school was done using the Tamil Nadu Water Fluoridation and Drainage Board field kit. Other factors that may have contributed to DF were assessed using a questionnaire, which was provided to each student. The data obtained were statistically analyzed using the SPSS software version 11.5. Statistical Analysis: Chi-square test was used for statistical analysis. Results: DF was present in 56.9% of the children examined. It was mostly seen in 9 years old (72%) and male (59%) children. A positive correlation was found between the occurrence of DF and the duration of residence in a place with high water fluoride content, consumption of borewell water (64%), the parts per million of fluoride in drinking water, consumption of black tea (59%). However, no correlation was found between DF, dental caries, consumption of milk, or consumption of foods cooked in aluminum vessels. Conclusion: There was a correlation between DF and factors such as male gender, bore well water consumption, black tea consumption and the duration of residence in a place with high water fluoride content.